Risk of Human Immunodeficiency Virus Acquisition Among High-Risk Heterosexuals With Nonviral Sexually Transmitted Infections: A Systematic Review and Meta-Analysis. Issue 6 (13th June 2022) - Barker, Erin K.; Malekinejad, Mohsen; Merai, Rikita; Lyles, Cynthia M.; Sipe, Theresa Ann; DeLuca, Julia B.; Ridpath, Alison D.; Gift, Thomas L.; Tailor, Amrita; Kahn, James G.
Abstract : We examine temporal relationships between heterosexual acquisition of nonviral sexually transmitted infections and human immunodeficiency virus, finding increased risk for women with Mycoplasma genitalium, gonorrhea, syphilis, trichomonas, or chlamydia and men with syphilis. Abstract : Background: Nonviral sexually transmitted infections (STIs) increase risk of sexually acquired human immunodeficiency virus (HIV) infection. Updated risk estimates carefully scrutinizing temporality bias of studies are needed. Methods: We conducted a systematic review (PROSPERO CRD42018084299) of peer-reviewed studies evaluating variation in risk of HIV infection among high-risk heterosexuals diagnosed with any of: Chlamydia trachomatis, Mycoplasma genitalium, Neisseria gonorrhoeae, Treponema pallidum, and/or Trichomonas vaginalis . We searched PubMed, Web of Science, and Embase databases through December 2017 and included studies where STIs and HIV were assessed using laboratory tests or medical examinations and where STI was diagnosed before HIV. After dual screening, data extraction, and risk of bias assessment, we meta-analytically pooled risk ratios (RRs). Results: We found 32 eligible studies reporting k = 97 effect size estimates of HIV acquisition risk due to infection with one of the abovementioned STIs. Most data were based on women engaged in sex work or other high-risk occupations in developing countries. Many studies did not measure or adjust for known confounders, including drug injection and condom use, and most were at medium or high risk of bias because of the potential for undetected HIV infection to have occurred before STI infection. Human immunodeficiency virus acquisition risk increased among women infected with any pathogen; the effect was greatest for women infected with Mycoplasma genitalium (RR, 3.10; 95% confidence interval [CI], 1.63–5.92; k = 2) and gonorrhea (RR, 2.81; 95% CI, 2.25–3.50; k = 16) but also statistically significant for women infected with syphilis (RR, 1.67; 95% CI, 1.23–2.27; k = 17), trichomonas (RR, 1.54; 95% CI, 1.31–1.82; k = 17), and chlamydia (RR, 1.49; 95% CI, 1.08–2.04; k = 14). For men, data were space except for syphilis (RR, 1.77; 95% CI, 1.22–2.58; k = 5). Conclusion: Nonviral STI increases risk of heterosexual HIV acquisition, although uncertainty remains because of risk of bias in primary studies.